Analysis of flow characteristics in the sewerage system of residential areas within Kuantan - Teh, Yun Qin (2016)
The evaluation of flow characteristic for sewerage systems analysis is essential in designing sewerage systems. Sewerage system plays an important role in collecting sewage from the community before transporting them to the sewerage treatment plant. Flow characteristics of sewage flow will be influenced by the population equivalent at the research area. There are several steps in measuring the flow characteristics which include collecting data in the manhole by using flowmeter and performing data analysis to investigate per capita flow, design criterion as well as peak flow factor. This study was carried out in three selected residential areas namely Taman Lepar Hilir Saujana (MH 84), Taman Pandan Damai (MH K) and Taman Bandar Putra (MH 92a). These locations are located in Kuantan, Pahang. From September 2015 to April 2016, this study was carried out in which the main equipment used is the ISCO 2150 area-velocity flowmeter and sensor. Equipment calibration was done in the Hydraulics and Hydrology Laboratory of UMP Gambang before the commencement of field work. In this study, sensor plays an important role in detecting the sewerage flow and generating the data for the flowmeter. Besides that, rainfall data collection was carried out to determine whether or not the flow rate is affected by the rain. Both data of flow rate and rainfall were retrieved using Flowlink 5.1 software. Data collected from the area-velocity flowmeter was converted into graph foam before the analysis. Data collection was performed on weekdays and weekends as well as during day time and night time. From this, data obtained will be divided into sets. One set of data is taken for a duration of two weeks with measurement done at every time interval of five minutes. The resulting analysis of flow characteristics obtained was compared with the standard limit stated in MS 1228:1991. Based on the MS 1228:1991, the per capita flow is 0.225 m3/day/person and design criterion is 4.7. In this case, per capita flow at Taman Lepar Hilir Saujana is lower than the Malaysia Standard. However, the results from Taman Pandan Damai and Taman Bandar Putra show higher values in that they are more than 0.225m3/day/person. In terms of design criterion, Taman Pandan Damai recorded lower than 4.7. In contrast, Taman Lepar Hilir Saujana and Taman Bandar Putra gave a higher value than 4.7. The results obtained will ease the researchers who are interested to further their study in this field.